Prices and the Guideposts: The Effects of Government Persuasion on Individual Prices - Alexander, Arthur J. (The Review of Economics and Statistics, 1971)
W AGE-PRICE guideposts were part of the government's economic policy from 1962 until the close of the Johnson Administration in 1968.' A particular method of policing the guideposts evolved during this period. The Administration sought, through public and private confrontations, to influence the pricing decisions of firms. We shall describe briefly this policy, propose several alternative hypotheses to explain the resultant behavior of firms, and analyze statistically those variables predicted to be associated with government success and failure in influencing firm behavior.